2013
DOI: 10.3189/2013jog12j108
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a time-lapse photograph analysis method to investigate the link between tidewater glacier flow variations and supraglacial lake drainage events

Abstract: Marine-terminating glaciers may experience seasonal and short-term flow variations, which can impact rates of ice flux through the glacier terminus. We explore the relationship between variability in the flow of a large tidewater glacier (Belcher Glacier, Nunavut, Canada), the seasonal cycle of surface meltwater production and the rapid drainage of supraglacial lakes. We demonstrate a novel method for analyzing time-lapse photography to quantify lake area change rates (a proxy for net filling and drainage rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
3
42
1
Order By: Relevance
“…The results presented here indicate that changes in basal water pressure leading to velocity changes of this magnitude can in fact have a strong influence on modelled calving rates. The finding supports previous tidewater glacier modelling work (Vieli et al, 2000) and observations at other tidewater glaciers (Kamb et al, 1994;Sugiyama et al, 2011;Danielson and Sharp, 2013) which had already observed a significant dynamic response to changes in basal water pressure, and highlights that changes in basal conditions should not be excluded as an important influence on tidewater glaciers. The link between changes in air temperature and run-off, and changes in velocity may, however, be complicated.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results presented here indicate that changes in basal water pressure leading to velocity changes of this magnitude can in fact have a strong influence on modelled calving rates. The finding supports previous tidewater glacier modelling work (Vieli et al, 2000) and observations at other tidewater glaciers (Kamb et al, 1994;Sugiyama et al, 2011;Danielson and Sharp, 2013) which had already observed a significant dynamic response to changes in basal water pressure, and highlights that changes in basal conditions should not be excluded as an important influence on tidewater glaciers. The link between changes in air temperature and run-off, and changes in velocity may, however, be complicated.…”
Section: Discussionsupporting
confidence: 80%
“…Selecting the values of cwd to use was challenging as no measurements of observed water depth have been published, and likely values are difficult to predict given the changing volume of crevasses as ice advects downstream, and the probable high rate of drainage in the fractured area around the terminus. Observations have shown that water-filled crevasses can occur even near the calving margin (Danielson and Sharp, 2013), so it is at least known that high water depths are possible in this region, and may become more frequent if the trend of increasing surface ablation continues. If a hydraulic connection exists between the glacier surface and the bed, surface meltwater can also affect the terminus behaviour by altering basal water pressure, and hence sliding velocity.…”
Section: Discussionmentioning
confidence: 99%
“…This water often contains entrained subglacial sediment, giving the lake a turbid appearance. Where such connections exist, the water level can be used as a measure of basal water pressure (Danielson and Sharp, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…glaciers. Both monosopic and stereoscopic modes have been used successfully in glaciological applications since the 90s (Harrison, 1992;Hashimoto et al, 2009;Ahn and Box, 2010;Svanem, 2010, Maas et al, 2010Rivera et al, 2012;Danielson and Sharp, 2013).…”
Section: Introductionmentioning
confidence: 99%